Gene–Environment Correlation Underlying the Association Between Parental Negativity and Adolescent Externalizing Problems - Marceau, Kristine (2013)
Studies of adolescent or parent-based twins suggest that gene–environment correlation (rGE) is an important mechanism underlying parent–adolescent relationships. However, information on how parents′ and children’s genes and environments influence correlated parent and child behaviors is needed to distinguish types of rGE. The present study used the novel Extended Children of Twins model to distinguish types of rGE underlying associations between negative parenting and adolescent (age 11–22 years) externalizing problems with a Swedish sample of 909 twin parents and their adolescent offspring and a U.S.-based sample of 405 adolescent siblings and their parents. Results suggest that evocative rGE, not passive rGE or direct environmental effects of parenting on adolescent externalizing, explains associations between maternal and paternal negativity and adolescent externalizing problems.